2008
DOI: 10.1103/physrevd.77.014037
|View full text |Cite
|
Sign up to set email alerts
|

Quarkonium production in coherent hadron-hadron interactions at the CERN LHC

Abstract: The photoproduction of quarkonium in coherent hadron-hadron (pp/pA/AA) interactions for LHC energies is an important tool to investigate the QCD dynamics at high energies. In this paper we estimate the integrated cross section and rapidity distribution for J/Ψ and Υ production using the Color Glass Condensate (CGC) formalism. We predict large rates, implying that the experimental identification could be feasible at the LHC.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
44
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 53 publications
10
44
3
Order By: Relevance
“…For related works in coherent interactions see Ref. [23]. Considering the requirement that photoproduction is not accompanied by hadronic interaction (ultraperipheral collision) an analytic approximation for the equivalent photon flux of a nuclei can be calculated, which is given by [5] …”
Section: Photoproduction Of Z 0 In Coherent Collisionsmentioning
confidence: 99%
“…For related works in coherent interactions see Ref. [23]. Considering the requirement that photoproduction is not accompanied by hadronic interaction (ultraperipheral collision) an analytic approximation for the equivalent photon flux of a nuclei can be calculated, which is given by [5] …”
Section: Photoproduction Of Z 0 In Coherent Collisionsmentioning
confidence: 99%
“…and this prescription has been used in many subsequent works [25][26][27][28][29]. It is motivated by the explicit perturbative analysis in [22] that such a phase factor arises in nonforward amplitudes ∆ ⊥ = 0.…”
Section: The Dipole S-matrix and The Gluon Gpdmentioning
confidence: 99%
“…In contrast, for the double J/ production, the contribution associated to the description of the QCD dynamics at high energies contributes significantly, mainly in pp collisions. Predictions for the RHIC, LHC, FCC, and CEPC-SPPC energies are shown.In recent years a series of experimental results from RHIC [1,2], Tevatron [3] and LHC [4][5][6][7][8][9][10][11][12] demonstrated that the study of photon-induced interactions in hadronic colliders is feasible and that it can be used to, among other things, improve our knowledge on the nuclear gluon distribution [13][14][15][16][17][18][19], on details of QCD dynamics [20][21][22][23][24][25][26][27][28][29][30], on the mechanism of quarkonium production [29][30][31][32][33][34][35][36], on the Odderon [37,38] and on the photon flux of the proton [39,40]. These data have stimulated the development of the theoretical description of these processes as well as the proposal of new forward detectors to be installed in the LHC [41,42].…”
mentioning
confidence: 99%